2006
DOI: 10.1080/10520290601065128
|View full text |Cite
|
Sign up to set email alerts
|

Histological and biochemical characterization of von Ebner's glands in the Syrian hamster; comparison with rat von Ebner's glands

Abstract: We report here for the first time a morphological description and observations on some of the secretory proteins of the von Ebner's lingual salivary glands (VEG) of the Syrian hamster. Hamster VEG were macroscopically less distinct, but histologically similar to rat VEG. VEG extracts of hamster and rat were assayed for lipase, alpha-amylase and peroxidase activities. Unlike rat VEG, which is rich in lipase activity, hamster VEG extract had no detectable lipase activity and did not react with antibodies to eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In some mammals (Tandler et al, ; Gargiulo et al, ; Pedini et al, ; Triantafyllou et al, , Paliwal et al, ), the histochemical data have revealed that neutral mucosubstances and sulphated mucins exist in both seromucous and von Ebner's glands (although their staining intensities differ); however, carboxylated mucins do not exist in either gland type. Functional considerations of these results indicate that differences in mucins secreted from glands, together with histomorphological differences in different parts of the tongue, reflect an adaptation to physiological requirements, including protection against bacterial colonization.…”
Section: Discussionmentioning
confidence: 99%
“…In some mammals (Tandler et al, ; Gargiulo et al, ; Pedini et al, ; Triantafyllou et al, , Paliwal et al, ), the histochemical data have revealed that neutral mucosubstances and sulphated mucins exist in both seromucous and von Ebner's glands (although their staining intensities differ); however, carboxylated mucins do not exist in either gland type. Functional considerations of these results indicate that differences in mucins secreted from glands, together with histomorphological differences in different parts of the tongue, reflect an adaptation to physiological requirements, including protection against bacterial colonization.…”
Section: Discussionmentioning
confidence: 99%
“…It follows that the minor salivary glands of rats also ought to have important physiologic roles. Some of these, such as digestion, taste, and salivary regulators of pH and oral fl ora, have been the subjects of considerable study, but mostly with VEG (DeNigris et al 1988, Hamosh and Scow 1973, Field and Hand 1987, Schmale et al 1990, Leinonen et al 2001, Paliwal et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…1). Survey photomicrographs showing the location of the glands have been published by Hand (1970) and Paliwal et al (2006); the latter paper also was illustrated with photographs showing the glistening gland bodies in a slice through the vallate papilla. The acini stain moderately with PAS (not illustrated), but do not stain with AB (Fig.…”
Section: Lingual Serous Glands Of Von Ebner (Veg)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is suspected that von Ebner’s glands differ from parotid glands in terms of the mechanism and role of amylase secretion. One immunohistochemical study involving an enzymatic method has been reported [24]. However, as far as we know, there is no report of the immunocytochemical localization of amylase in von Ebner’s glands.…”
Section: Introductionmentioning
confidence: 99%